2017
DOI: 10.1007/s11356-017-0402-7
|View full text |Cite
|
Sign up to set email alerts
|

NO2 inhalation enhances asthma susceptibility in a rat model

Abstract: Nitrogen dioxide (NO) is a major air pollutant. Epidemiologic studies have found that NO exposure is associated with an increased risk of asthma. Nevertheless, the potential molecular mechanisms remain unclear. In this study, we investigated the effect of NO inhalation on the occurrence of allergic airway inflammation and its underlying mechanisms. Firstly, male Wistar rats were exposed to 2 and 5 mg/m NO (28 days, 5 h/day). The results showed that NO exposure could induce pulmonary inflammatory response, mucu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…31 There is also mechanistic evidence showing the capacity of gaseous pollutants to enhance pro-allergenic immune pathways. 32 Epidemiologic studies support this mechanistic research. For example, Patel et al 33 found that proximity to major roads was associated with increased serum total IgE in young children in New York City, whereas Rage et al 34 found an association between ozone concentrations at residential addresses and total IgE in adults with asthma in France.…”
Section: Effects On Allergic Sensitizationmentioning
confidence: 79%
See 1 more Smart Citation
“…31 There is also mechanistic evidence showing the capacity of gaseous pollutants to enhance pro-allergenic immune pathways. 32 Epidemiologic studies support this mechanistic research. For example, Patel et al 33 found that proximity to major roads was associated with increased serum total IgE in young children in New York City, whereas Rage et al 34 found an association between ozone concentrations at residential addresses and total IgE in adults with asthma in France.…”
Section: Effects On Allergic Sensitizationmentioning
confidence: 79%
“…54 Allergic sensitization and Th2-biasing of immune responses itself increase susceptibility to viral respiratory infections. 3,4 However, air pollution also has multiple actions to increase susceptibility to and harm from respiratory tract infections (Table 1 26,32,[55][56][57][58] ).…”
Section: Effects On Antiviral Immunitymentioning
confidence: 99%
“…Previous study showed that particulate matter exposure induced inflammatory cell infiltration and hyperemia in the lung tissues, increased the inflammatory cell numbers and promoted the expression of pro-inflammatory mediators (TNF-α, IL-1β, IL-6) [39]. Some studies have shown that gaseous pollutants (SO 2, NO 2 ) exposure could induce pulmonary inflammatory response and pulmonary pathological changes [46,47].…”
Section: Tablementioning
confidence: 99%
“…A study showed that when Sprague-Dawley rats exposed to SO 2 acutely, acute inflammation with neutrophil and macrophage airway infiltration was presented and inflammatory infiltrates remained in lung tissue for at least 14 days[6]. Previous research has established that NO2 exposure could induce pulmonary inflammatory response, mucus formation, and Th1/Th2 imbalance in control group[7]. It was reported that sex differences in acute O3-induced airway physiology responses and airspace influx without significant difference in other injury and inflammation measures[8].…”
Section: Introductionmentioning
confidence: 99%